Age of Occurrence and Severity of Childhood Sexual Abuse: Impacts on Health Outcomes in Men Who Have Sex with Men and Transgender Women. Issue 6 (24th July 2021) - Xavier Hall, Casey D.; Moran, Kevin; Newcomb, Michael E.; Mustanski, Brian
ABSTRACT: Childhood sexual abuse (CSA) is associated with a wide range of health outcomes and is more prevalent among men who have sex with men (MSM) compared to men who have sex with women exclusively and among transgender women (TW) compared to cisgender peers; however, there is a lack of consensus regarding an explanatory theoretical model. This analysis examined these models across health outcomes using baseline data from a longitudinal study of MSM and TW in Chicago (n = 1, 035) collected from 2015 to 2019. Severity of CSA was measured for two age ranges (prior to 13 and 13–17). Logistic regression and negative binomial regressions were estimated. Teenage experiences of CSA were associated with alcohol problems, cannabis problems, suicide ideation/attempt, depression, condomless anal sex partners, rectal STI, and HIV. Pre-teenage CSA was associated with alcohol use and depressive symptoms. Significant interactions across age of experience of CSA were found for alcohol problems, cannabis problems, and condomless anal sex partners. Consistent with previous literature, this analysis found CSA to be a significant influence on various health outcomes. No single explanatory framework emerged; however, adolescent exposures may be more closely linked to health outcomes and risk behaviors than pre-teenage or cumulative exposures.